Cultural and Social Influences on Vasectomy Acceptance Among Married Men and Women in Rural Kenya - OWINO ABUNGU, Domnick; KIPSANG, Ezekiel; CHEPOWON, Faith; JEPNGETICH, Abishak (East African Journal of Nursing, 2025)
Despite vasectomy being one of the most effective and permanent methods of contraception, its uptake remains extremely low in many African settings. In Kenya, cultural, religious, and gender-based perceptions continue to hinder male involvement in family planning. This study explored the cultural and social factors that influence vasectomy acceptance among married men and women in Kampi Ya Moto, a rural community in Nakuru County, Kenya. The study employed a qualitative exploratory design grounded in phenomenological inquiry. A purposive sample of 18 married men and women aged 18 years and above, with at least two children, was selected. Data were collected through in-depth semi-structured interviews and analyzed thematically using Braun and Clarke’s six-step approach. Trustworthiness was ensured through credibility, transferability, dependability, and confirmability strategies. Three major themes emerged: (1) Perceptions of masculinity and gender roles, vasectomy was widely seen as a threat to male identity, with fertility equated to manhood and social dominance; (2) Religious and spiritual beliefs, participants believed that permanent contraception contradicted divine will, often reinforced by limited exposure to formal family planning education; and (3) Community norms and misinformation, widespread myths linked vasectomy to impotence, weakness, or castration, discouraging interest and uptake. Nonetheless, a subset of participants, especially women, showed conditional acceptance, expressing willingness if accurate information and spousal consensus were available. Vasectomy acceptance is constrained by deeply rooted sociocultural narratives, gender norms, and religious doctrines. However, emerging openness suggests potential for change. Community-based education, male-inclusive counseling, and strategic engagement with religious and cultural leaders are recommended to promote informed decision-making and enhance male participation in family planning in rural Kenyan contexts.